2012
DOI: 10.2341/11-137-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prewarming and/or Delayed Light Activation on Resin-Modified Glass Ionomer Bond Strength to Tooth Structures

Abstract: Bond strength might improve by delaying the light activation procedure when a cavity conditioner is used for bonding RMGI to enamel. Conversely, delaying the light activation and/or prewarming of RMGI compromises bond strength to dentin and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Although the ISO 4049 specification is largely used for testing composites that are lightcured only, the technique recommended for specimen preparation hinders the evaluation of the possible effects of light-activation moment on mechanical properties of dual-cured resin-based materials (MORAES, et al 2009;FARIA-E-SILVA, et al 2011;KHOROUSHI, et al 2012;FARIA-E-SILVA, et al 2012;SOUZA, et al 2013;FARIA-E-SILVA, et al 2014) By the time dual-cured materials are inserted into the mold, the polymerization reaction has already started via chemical activation. Therefore, each light-activation is performed over areas of the polymer, presenting with differences in the degrees of C=C conversion impairing the standardization of time for light-activation (FARIA-E-SILVA, et al 2012;KHOROUSHI, et al 2012).…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…Although the ISO 4049 specification is largely used for testing composites that are lightcured only, the technique recommended for specimen preparation hinders the evaluation of the possible effects of light-activation moment on mechanical properties of dual-cured resin-based materials (MORAES, et al 2009;FARIA-E-SILVA, et al 2011;KHOROUSHI, et al 2012;FARIA-E-SILVA, et al 2012;SOUZA, et al 2013;FARIA-E-SILVA, et al 2014) By the time dual-cured materials are inserted into the mold, the polymerization reaction has already started via chemical activation. Therefore, each light-activation is performed over areas of the polymer, presenting with differences in the degrees of C=C conversion impairing the standardization of time for light-activation (FARIA-E-SILVA, et al 2012;KHOROUSHI, et al 2012).…”
Section: Thementioning
confidence: 99%
“…Therefore, each light-activation is performed over areas of the polymer, presenting with differences in the degrees of C=C conversion impairing the standardization of time for light-activation (FARIA-E-SILVA, et al 2012;KHOROUSHI, et al 2012). Using single light-activation in the center of the specimen with the tip of the light-curing unit, away from the composite, is an alternative.…”
Section: Thementioning
confidence: 99%
“…This may be the result of enhanced micromechanical retention due to improved removal of the smear layer and dentinal plugs which allowed resin monomer (HEMA) penetration into the dentinal tubules. Additionally, EDTA does not alter the fibrillar structure of collagen, allowing the mineral content of collagen to bond with the ionic component of RMGIs (8) and since the structural support by the mineral is not missing, resin infiltration may be facilitated (9) .…”
Section: The Higher Bond Strength Of Photac Fil Quickmentioning
confidence: 99%
“…On the other hand, using of G1 and resin modified glass ionomer have been used as an alternative to resin based cement [17][18][19]. Researchers showed that resin-modified glass ionomer cements have stronger bonding when compared to conventional glass ionomer bonding [20,21]. …”
Section: Introductionmentioning
confidence: 99%